Factors Influencing Public Perception of Waste Separation at Source in Kathmandu Valley - Singha, Manisha; Danuwar, Ranjana Kumari; Paudel, Udaya Raj (NCC Journal, 2025)
Due to inadequate planning, limited awareness among residents, and insufficient resources, local municipal authorities face significant challenges in effectively managing solid waste, which has resulted in issues such as flooding and waterlogging. This study aims to develop a comprehensive understanding of the factors influencing people’s perceptions of waste separation at the source. In addition, it seeks to identify the key challenges hindering the adoption of waste separation practices and to propose effective measures to support and enhance their implementation. This study adopts an explanatory research design. The research draws upon a comprehensive analysis of empirical studies and employs descriptive and inferential statistics to analyze the data collected from the general population in Kathmandu valley. Convenience sampling is employed to gather responses, resulting in a sample size of 419 participants. The data collection process utilizes self-administered questionnaires facilitated by the KOBO toolbox. Structural Equation Modeling (SEM) is utilized to analyze the perceptions of individuals regarding waste separation at the source. The findings reveals that attitude, perceived behavioral control, and moral norm significantly influence intention, while subjective norm does not. Furthermore, intentions have a significant impact on waste separation behavior. The study also identifies common challenges faced by respondents, including lack of education and awareness, financial incentives, access to infrastructure and facilities, availability of segregation-related materials, and inconsistent waste collection systems. To address these challenges, it is recommended to ensure easy availability of segregation-related resources, implement education and awareness programs, establish a consistent waste collection system, provide access to infrastructure and facilities, and incentivize good waste management practices. The study revealed that attitude, perceived behavioral norm, moral norm, and intention influences waste separation behavior. Furthermore, peoples face significant challenges such as lack of education and awareness, financial incentives, access to infrastructure and facilities, availability of plastics, bins and containers and inconsistent waste collection system.